Implementasi Manajemen Kurikulum Merdeka Sebagai Upaya Peningkatan Mutu Pendidikan - Alex Chanra Gultom, Jhunri; Danim, Sudarwan; sumarsih (Manajer Pendididikan, 2024)
This study aims to describe the implementation of transform curriculum management as an effort the quality of education at Senior High School 1 Kaur and Senior High School 3 Kaur. The research uses a qualitative descriptive method. The research subjects were the School Principal, deputy Principal for curriculum, and teachers at Senior High School 1 Kaur and Senior High School 3 Kaur. Research data was obtained from interviews, observations, and documentation. Based on the research results, The implementation of the transform curriculum in Senior High School 1 Kaur dan Senior High 3 Kaur has had a positive impact on improving the quality of education, particularly in the areas of curriculum planning, curriculum implementation, curriculum evaluation, and follow-up evaluation.